G518(P) An ethical approach to patient and public involvementwith children and young people. (24th May 2017) - Mitchell, S; Nadeem, S; Khan, D; Boora, R; Coad, J; Slowther, AM; Dale, J
Abstract : Aims: Patient and public involvement (PPI) in research is important to add relevance and context. No formal ethical approval is required, however in sensitive research subject areas, there are potential ethical issues that could arise from PPI. In particular, research concerning palliative care requires discussion about the end of life and dying, which can cause distress. The aim of this abstract is to outline the development of an ethical approach to PPI with children and young people (CYP) for palliative care research. Methods: The approach was informed by quality checklists for PPI and by drawing on broad ethical principles; benefits and risks to participants, and the responsibilities attached to relationships with both participants and the wider community when conducting an activity. Funding for the PPI work was secured as part of an NIHR Doctoral Research Fellowship. Results: Benefits for PPI participants were identified as learning new skills, working with others and contributing to an original piece of research. Processes were developed in order to minimise the risk of distress, by outlining clear aims, benefits and risks are for the PPI work at each group meeting, providing written resources, and asking for verbal consent before proceeding. Younger group members were encouraged to discuss their involvement with their parents. Access to debrief and support from youth workers was made available, if necessary. Young people have offered honest constructive feedback on the project, and expect that this is listened to. This requires a clear commitment from the researcher to act on feedback and use it to inform work appropriately, while at the same time managing the expectations of the group. PPI has informed literature reviews, study design, the development of resources for participants, applications for ethical approval and plans for dissemination. There has been a request for social media interaction through Twitter. Conclusion: PPI is an integral part of research. Involving young people as peers provides the benefit of being able to design research from their perspective. Planning an ethically sound approach minimises risks to PPI group members. The approach described here was developed for palliative care research but can be applied more broadly.